Discrimination, bullying or harassment in undergraduate education in the osteopathic, chiropractic and physiotherapy professions: A systematic review with critical interpretive synthesis - Andrew MacMillan; David Hohenschurz-Schmidt; Dr Valentina Migliarini; Dr Jerry Draper-Rodi (International Journal of Educational Research Open, 2022)
The objective of this review was to chart, appraise and synthesise the available evidence regarding the experience of discrimination, bullying or harassment in undergraduate manual therapy (MT) education.We systematically searched 9 databases in accordance with our prospectively registered protocol (PROSPERO CRD42021249305).English language primary research papers relevant to concepts of discrimination, bullying or harassment in undergraduate MT education, published between 2010 and 2021, were sought. Two independent reviewers screened all titles and abstracts against inclusion criteria, full texts were then retrieved and independently screened and assessed for risk of bias and data extraction. Disagreements were resolved by discussion and the use of a third reviewer. Data were synthesised using a critical interpretive synthesis method.We identified 407 records in our search, 17 full text articles were included in our final synthesis. We highlighted that bullying is prevalent within undergraduate MT education. This is reported to have a large impact upon learners' wellbeing and attainment. Attainment gaps and higher attrition rates for students from ethnic minority groups and students with disabilities in UK physiotherapy were noted in our review, this may not be applicable to other contexts. Our review was limited to English language and a lack of available primary data may be a limitation of our review. This is the first systematic review on this topic and followed best available methodological guidance.